AKUISISI DATA ENCODER ABSOLUT SPEKTROMETER NEUTRON TIGA SUMBU MENGGUNAKAN NI USB-6351 DAN BAHASA PEMROGRAMAN LabVIEW - Ari Fiyanti; Sri Wahyu Suciati; M. Refai Muslih (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
DATA ACQUISITION ABSOLUTE ENCODER A TRIPLE AXIS NEUTRON SPECTROMETER USES NI USB-6351 AND LABVIEW PROGRAMMING LANGUAGE. This encoder is used to monitor the position and rotation of the analyzer crystal scattering arm of TAS. Digital signals from the absolute encoder had been used into the computer via NI USB-6351. Program language LabVIEW is used to acquire process the data ported and deliver the results to the user. Keywords: Absolute Encoder, NI USB-6351, LabVIEW.